OPTIMIZATION OF MEDICAL EVALUATION STRATEGIES IN VACCINATED WOMEN ANTI COVID-19, IN ROMANIA, TO IMPROVE THE LEVEL OF HESITATION AGAINST THE BENEFIT OF VACCINATION - Andreea Roxana Luca; Ramona Elena Teiu; Tudor Florin Ursuleanu; Roxana Grigorovici; Hlescu Cristian Stefan; Maria Paula Comanescu; Alina Ionela Calin; Alexandru Grigorovici (Romanian Journal of Oral Rehabilitation)
Aim of the study. In December 2020, the first two mRNA vaccines, developed by Pfizer/BioNTech and Moderna, were approved by the FDA in the USA. Clarification about the safety, efficacy, and low rate of adverse reactions of COVID-19 vaccines was not sufficient to alleviate the level of hesitation against vaccination in the global community. Materials and methods. In medical practice in Romania, patients who presented to the gynecological consultation have blamed changes in the duration, appearance of menstruation and menstruation cycle, along with other new symptoms that they considered to be post-vaccination anti COVID-19. This aspect required a survey. The general principles of the strategy will continue to apply, namely, the continuation of screening by popularizing the survey with the aim of raising patient awareness and increasing timely addressability to avoid complications. Results Lowering the level of hesitation to the susceptibility to vaccination and increasing confidence in the vaccination campaigns against COVID-19 were identified as key outcomes. Conclusions The findings highlight the importance of addressing concerns regarding post-vaccination symptoms to improve public trust and participation in vaccination campaigns